UTILISING DIGITAL MEDIA TOOLS TO FOSTER INDIGENOUS COMMUNICATION SYSTEMS IN NIGERIA - Eke, Chigozi; Opeyemi Adeyemi, Muideen (African Journal of Social and Behavioural Sciences, 2024)
This study identified the digital media tools as channels for fostering indigenous communication systems in Nigeria. The theoretical framework of the study was drawn from cultural modernisation theory and media technological determinism theory. The study employs a comprehensive literature review to explore how digital media tools can foster indigenous communication systems in Nigeria (desk review). This method involved a literature review or secondary data analysis, involves the systematic collection, analysis, and interpretation of existing research, reports, publications, and other relevant documents. Findings from the study revealed that while these traditional forms of communication remain vital within communities, particularly in rural areas, their representation on digital media platforms is still limited and often misrepresented. The digital divide and dominance of Western-centric content have contributed to the underrepresentation and potential dilution of Nigeria's rich cultural heritage online. The study concluded that while traditional forms of communication continue to play a crucial role in fostering communal interactions, especially in rural areas, their presence on digital media platforms is sparse and often inaccurately portrayed, risking the loss of authenticity and cultural significance. The study recommended that digital media platforms have to collaborate with cultural custodians to ensure accurate representation and amplification of indigenous communication systems in the digital space.